A COMPARATIVE CLINICAL STUDY ON WITHDRAWAL SYMPTOMS OF MADATYAYA WITH PUNARNAVADI GHRITA - Kumar Satbir, *Chawla; Dr, Priyanka; Sonia, Dhiman; Ajay, Kumar (AYUSHDHARA, 2017)
The disease caused by the excessive and regular us of Madya is called Madatyaya which can be correlated to Alcoholism on basis of withdrawal symptoms. In present world of modernisation the unlimited pressure of carrier and livelihood the youth and middle age generation easily get addicted to alcohol which is a big hazard to social and economic development and deteriorates the health services. The addicted alcoholic patients cannot come out of the condition easily because the withdrawal symptoms. The present study has been done to manage the withdrawal symptoms of Madatyaya. In this study the clinical efficacy of medicine given by the Drug De-addiction centre and Punarnavadi Ghritt was compared on 20 patients of withdrawal symptoms divided in 2 groups i.e. A and B for 30 days. Hb gm%, TLC, DLC, ESR, LFT were also done to assess the efficacy of the drug. Group-A was treated with the medicine provided by the Drug De-addiction centre, which was statistically significant (P<0.05) in subjective parameters. Group-B treated with Punarnavadi Ghritta, showed significant (P<0.05) results in objective parameters. Follow-up was on 15th day and after treatment. Our study revealed that the test drug Punarnavadi Ghritta is more effective on objective parameters than modern medicine which is more effective on subjective parameters in treatment of withdrawal of Madatyaya. Hence the trial drug can be used as a medicine to improve laboratory findings for patients of withdrawal symptoms of Madatyaya.